Atomic-level characterization of the oxygen storage material YBaCo4O7+δ synthesized at low temperature. Issue 43 (12th October 2022) - Huang, Hsin-Hui; Kobayashi, Shunsuke; Tanabe, Toyokazu; Komiyama, Kaihei; Saito, Miwa; Motohashi, Teruki; Kuwabara, Akihide
Abstract : Low-temperature synthesis of YBaCo4 O7+ δ leads to the formation of nanosized particles and stacking faults with specific oxygen storage properties. Abstract : The oxygen storage material, YBaCo4 O7+ δ (YBCO), synthesized at a low temperature of 800 °C, shows extremely fast oxygen absorption/desorption with moderate oxygen storage capacity. Before exploiting the potential use in oxygen-related applications, a comprehensive study of its crystal and electronic structures at the atomic scale is beneficial. Here, using scanning transmission electron microscopy, we find that stacking faults are formed and randomly distributed throughout the particle. Electron energy loss spectroscopy reveals that the surface layer contains a higher oxidation state of cobalt (+3), which is significantly different from the inner part (lower oxidation state of cobalt). Combining the observed structural features with the oxygen storage performance, we suggest that structural defects and surface state govern the amount of oxygen that can be stored, while the surface area determines the oxygen absorption/desorption kinetics. This work provides insights into the structure–property relationship, leading to a better understanding of the design of oxide materials with promising oxygen storage properties.